The Influence of Social Media Marketing on Consumer Purchasing Decisions at Wilietta Store in Soppeng Regency - Puji Rahmah; Widia Widia; Nurul Awalia Ramadani; Asnia Minarti (GENTARA: management and accounting research, 2026)
This study aims to analyze the effect of social media marketing on consumer purchasing decisions at Wilietta Store in Soppeng Regency. Wilietta Store is a fashion business targeting women, especially young people who are active on social media. The use of social media as a marketing tool is considered important in attracting consumer attention and influencing purchasing behavior. This research uses a quantitative approach with a survey method by distributing questionnaires to Wilietta Store consumers. The independent variable in this study is social media marketing, while the dependent variable is purchasing decisions. The data were analyzed using statistical techniques to determine the relationship and influence between variables. The results of the study show that social media marketing has a positive and significant effect on consumer purchasing decisions. This indicates that the better the social media marketing strategy implemented, the higher the likelihood of consumers making a purchase. Therefore, social media marketing is an important factor in increasing sales and attracting consumer interest in the fashion industry